Coaxial Circular Jet Flows with Conical Attachments - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
This study is devoted to experiments on jet flows, which have many application areas. It shows the obtained jet flow structure. The experiments were carried out in a subsonic sucking wind tunnel having cross-section of 32 x 32 cm(2), length of 75 cm, and turbulence densities of 0.5%. One-channel hot-wire anemometer (HWA) was used in measurements. For circular jet, a steel pipe was used with a length of 120 cm and a diameter of 8 mm. Air generator was used for generating air into the jet flow and measurements were done at different jet flow velocities. Moreover, a conical diffuser with a length of 21 cm and 6 degrees slope was attached to the nozzle exit and effect of this diffuser on jet flow was examined. Seven types of measurement in three different categories were carried out. In experimental studies, velocity and turbulence distribution, axial velocity variation, jet half widths and, using these, jet diffusion rates and angles were measured. Moreover, flow analyses were done by drawing moment and frequency distribution for measurement sensitivity. These experimental results were compared with the studies on jet flow.